Marketing Efficiency of Cassava in Tulang Bawang Barat Lampung Province - Lidya Sari Mas Indah; Wan Abbas Zakaria; Teguh Endaryanto; Dewi Mulia Sari (Penerbit Goodwood, 2025)
Purpose: This study examines cassava marketing channels and their efficiency in Lampung Province, Indonesia. Lampung was selected purposively because it is Indonesia’s largest cassava-producing province. Research: The research was conducted from October 2020 to July 2021 using a survey approach at cassava production centers across Lampung. The respondents consisted of 100 cassava farmers selected through simple random sampling, while lapak (collectors) and agents were identified using snowball sampling. Marketing channels were mapped using a qualitative descriptive analysis. Marketing performance and efficiency were evaluated using marketing margin analysis, farmer share, and the Profit Margin Ratio (RPM). Results: The study identified multiple marketing channels, with the longest being the Farmer–Lapak–Agent–Factory channel. Overall, the cassava marketing system in Lampung was found to be inefficient, as indicated by relatively high marketing margins, low farmer share, and uneven profit margin ratios across marketing actors. Conclusions: Cassava marketing in Lampung is dominated by long distribution chains that reduce farmers’ benefits and create unequal profit distribution. Improving efficiency requires shortening marketing channels and strengthening farmers’ market access to increase the farmer’s share and reduce excessive margins. Limitations: The findings are based on survey data from selected cassava production centers during 2020–2021 and may not fully capture seasonal price dynamics, contract arrangements, or variations across other provinces. Contributions: This study provides empirical evidence on cassava marketing channel structures and efficiency indicators in Indonesia’s main production region, offering practical insights for designing interventions to reduce margins, improve farmer share, promote a more balanced profit distribution among supply chain actors.